Formulation development of lipid polymer hybrid nanoparticles of doxorubicin and its in-vitro, in-vivo and computational evaluation - Shafique, Muhammad; Ur Rehman, Maqsood; Kamal, Zul; Alzhrani, Rami M.; Alshehri, Sameer; Alamri, Ali H.; Bakkari, Mohammed Ali; Sabei, Fahad Y.; Safhi, Awaji Y.; Mohammed, Ahmed M.; Hamd, Mohamed A. El; Almawash, Saud (Frontiers in Pharmacology, 2023)
The purpose of this study was to assess the parameters of doxorubicin (DOX) loaded lipid polymer hybrid nanoparticles (LPHNs) formulation development, and then the bioavailability of DOX were determined in the rabbit model, in order to evaluate the intrinsic outcome of dosage form improvement after the oral administration. LPHNs were prepared by combine approach, using both magnetic stirring and probe sonication followed by its characterization in terms of size-distribution (Zeta Size), entrapment efficiency (EE), loading capacity, and the kinetics of DOX. LPHNPs were further characterized by using scanning electron microscopy (SEM), powder X-Ray diffractometry (P-XRD), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), in vitro and in vivo studies. The molecular modeling was determined through the density functional theory (DFT) simulations and interactions. DOX loaded and unloaded LPHNs were administered orally to the rabbits for bioavailability and pharmacokinetic parameters determinations. The plasma concentration of DOX was determined through high performance liquid chromatography (HPLC). The average size of DOX-loaded LPHNs was 121.90 ± 3.0 nm. The drug loading of DOX was 0.391% ± 0.01 of aqueous dispersion, where its encapsulation efficiency was 95.5% ± 1.39. After oral administration of the DOX-LPHNs, the area under the plasma drug concentration-time curve (AUC) improved about 2-folds comparatively (p < 0.05). DFT simulations were used to understand the interactions of polymers with different sites of DOX molecule. The larger negative binding energies (−9.33 to −18.53 kcal/mol) of the different complexes evince that the polymers have stronger affinity to bind with the DOX molecule while the negative values shows that the process is spontaneous, and the synthesis of DOX-LPHNs is energetically favorable. It was concluded that DOX-LPHNs provides a promising new formulation that can enhance the oral bioavailability, which have optimized compatibilities and improve the pharmacokinetic of DOX after oral administration.